Grammar for young learners. - Lewis, Gordon, ....-; Mol, Hans, ....- (Oxford : University Press, 2009)
Helps teachers of young learners introduce and practise grammar in a fun and motivating way. Steers a middle course between grammar-based and communicative approaches to teaching: meaning is the main focus of all language teaching and grammar is an intrinsic part of making meaning explicit. Key features: > Ready-made, enjoyable grammar activities to supplement coursebooks. > Strengthens grammatical accuracy in a fun and purposeful way. > Activities focus on key grammatical points for young learners and align with the CEF. > Contents organized by communicative goal (e.g. talking about the past), cross-referenced to grammar teaching point (e.g. past simple). > Includes activities for different learning styles. > Promotes critical and creative thinking skills and language awareness. > Photocopiable worksheets for many of the activities.
Keywords: Engels -- Didactiek; Engelse spraakkunst